The need for Islamic premarital counseling in Indonesia by professional school counselors - Sutoyo, Anwar; Saraswati, Sinta; Muslikah, Muslikah; Supriyanto, Agus (Journal of Professional Teacher Education, 2023)
The challenges of premarital counseling arise due to early marriage, divorce, marriage due to prior pregnancy, or various partner problems. As educators for students and prospective couples, counselors can conduct premarital counseling based on needs. The premarital counseling model has yet to be formed for the profession's development, so this study aims to analyze the needs of premarital counseling. The research method type is quantitative descriptive, with 21 students as subjects and a purposive sampling technique. The research instrument was an open questionnaire analyzed using quantitative description through percentages. The results of the study found five basic and salient needs for premarital counseling regarding the conditions for pillars of marriage to be valid, knowledge to form a happy family, setting goals for marriage, selecting criteria for a good husband/wife candidate in religion, and understanding the wisdom behind the prohibition to marry individuals who different faiths. Premarital counselors, as educators who are Islamic, competent, professional, and have integrity, use the Al-Qur'an and Sunnah in answering life's problems with a positive counseling mindset so that they know the relationship with God, application in life, awareness, and meaningful self-quality. The five needs of premarital counseling with an Islamic approach are the basis for developing a premarital counseling model with an Islamic system to be implemented in group and individual counseling. The design of Islamic premarital counseling can be designed for the prevention of early marriages and unwanted cases.